Venlafaxine-induced psychotic symptoms - Safeekh, A. T. (Medknow Publications, 2009)
Venlafaxine, an antidepressant belongs to Serotonin Norepinephrine Reuptake Inhibitors (SNRI), blocks the synaptic reuptake of serotonin in lower doses and also blocks reuptake of norepinephrine in higher doses. In addition it also blocks dopamine reuptake in still higher doses. This last mechanism of action is found to cause psychotic symptoms. Very few cases are reported with this adverse effect of venlafaxine. Here is a case report where a 32 year-old male with social phobia developed delusions of persecution on two occasions when he was put on venlafaxine 150 mg/day, which responded to withdrawal of venlafaxine and a short course of antipsychotics. The delusions never reappeared when he was maintained on escitalopram.